COR388 (atuzaginstat): an investigational gingipain inhibitor for the treatment of Alzheimer disease. (3rd October 2022) - Sabbagh, Marwan N.; Decourt, Boris
ABSTRACT: Introduction: Evidence from in vitro and in vivo studies demonstrates that amyloid beta (Aβ) oligomers have potent, broad-spectrum antimicrobial properties created by fibrils that entrap pathogens and disrupt their membranes. Data suggest that Aβ may play a protective role in the innate immune response to microbial infections and that Aβ in the brain plays a damaging role when the inflammatory response is not well controlled. Areas covered: This paper describes the relationship between periodontal disease and Alzheimer disease (AD), the role of Porphyromonas gingivalis and its secreted gingipains in AD, and the potential of the gingipain inhibitor atuzaginstat (COR388) to modulate AD neuropathologies. Expert opinion: P. gingivalis is opsonized by Aβ42, is capable of entering the brain, and is an accelerant of neuropathologies in rodent models of AD. Thus, in our opinion, this bacteria is highly likely to be a pathogen capable of initiating or precipitating the progression of AD, which agrees with the pathogen hypothesis of clinical AD development.